Penguatan Partisipasi dan Dinamika Kelompok Peternak Sapi PO Kebumen di Kabupaten Kebumen - Prisma Asih Kinanthi; Mochamad Sugiarto; Masrukin Masrukin (Jurnal READ (Research of Empowerment and Development), 2021)
The Decree of the Minister of Agriculture of the Republic of Indonesia Number 385 / Kpts / PK.040 / 6/2015 stipulates that PO cattle. Livestock groups have an essential role in increasing the population of PO Kebumen cattle, but the number of herds is stagnant. The lack of additional cattle herd in PO Kebumen is a challenge currently facing. The success in encouraging participation to improve group dynamics is expected to strengthen group institutions and realize group sustainability. This study aims to: 1) Describe the level of the involvement of PO Kebumen cattle breeders in the activities of the PO Kebumen cattle breeders group, 2) Describe the level of group dynamics in the PO Kebumen cattle breeders group, 3) Analyze the relationship between breeders age, breeders type, and farmer education with participation and group dynamics, 4) Analyzing the relationship between farmer participation and group dynamics of PO Kebumen cattle breeders. The research method used is a survey method. Determination of respondents using the multistage sampling method and obtained 65 respondents of livestock members. The data analysis method used was descriptive analysis to describe the profile of the OD Kebumen farmers, the level of participation, and the level of group dynamics. Spearman rank correlation analysis was used to analyze the relationship between farmer characteristics, including age, education, and group experience with farmer participation and group dynamics. The results showed that 1) The participation rate of the PO cattle group in Kebumen was in a low category; more than 60% of group members stated that planning, implementation, monitoring, and utilization were still intense. 2) The dynamic level of the PO cattle herd in Kebumen Regency is still low. The results of the data analysis of the total score of 38 with a presentation of 59% of livestock members stated that the level of group dynamics was still in the low category. 3) Age of breeders, husbandry education, and farmer experience did not significantly correlate with the level of participation and the level of group dynamics (P> 0.05). 4) The relationship between the level of participation and the level of group dynamics, the low level of participation is significantly positively related to the low level of group dynamics of 0.317 * (P <0.05).